Beyond T Cells: Understanding the Role of PD-1/PD-L1 in Tumor-Associated Macrophages - Lu, Di (J Immunol Res, 2019)
Programmed cell death protein 1 (PD-1) and its ligand PD-L1 have attracted wide attention from researchers in the field of immunotherapy. PD-1/PD-L1 have been shown to exist in many types of cells in addition to T lymphocytes, and studies have accordingly extended from their suppressive effect on T cell activation and function to examining their role in other cells. In this review, we summarize recent research on PD-1/PD-L1 in macrophages, with the aim of furthering our understanding of PD-1/PD-L1 and their detailed roles in macrophages. This information may provide additional insights for researchers, enrich the basic theory of anti-PD-1/PD-L1 immunotherapy, and thus ultimately benefit more patients.